2014
DOI: 10.1016/j.jsps.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Skin care: Historical and contemporary views

Abstract: Primary prevention, specifically skin care, is an important principle in Islamic theology just as it is emphasized in contemporary medicine. Many skin diseases can be prevented by a proactive approach to skin care, such as proper hygiene and routine inspections, principles that are constantly highlighted in the Islamic literature. Islam promotes primary prevention of disease, including recommendations for skin care practices. The recommendations for skin care practices in Islamic teachings are analogous to cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…While there are some research reports in the literature, the majority of these focus on Caucasian, college-aged women from the U.S [ 5 ]. The religious etiquettes of Islam specify that removal of pubic hair should be initiated at menarche, and done at least once every 40 days [ 13 , 20 ]. Accordingly, we found that all respondents removed their pubic hair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are some research reports in the literature, the majority of these focus on Caucasian, college-aged women from the U.S [ 5 ]. The religious etiquettes of Islam specify that removal of pubic hair should be initiated at menarche, and done at least once every 40 days [ 13 , 20 ]. Accordingly, we found that all respondents removed their pubic hair.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reasons exist for removing pubic hair, including hygiene, comfort, aesthetic reasons, sex appeal (often associated with being partnered), receiving cunnilingus, having looked at one’s genitals in the previous 4 weeks, and some may feel pressured by family or friends to participate in hair removal practices [ 5 7 , 12 ]. While religion has not yet been examined related to pubic hair removal, in Muslim culture today, both men and women are encouraged to remove armpit and pubic hair [ 13 ]. A recent study in Turkey found that the vast majority of Turkish Cypriot women regularly removed their pubic hair [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…5(2), 400-405 401 The skin, is the body's largest organ, it helps to secure the integrity of the host and at the same time, allows the individual to communicate with the outside world. (1) Skin care is an essential part of personal hygiene and well-being. The proper care of skin is important as unclean skin favors the development of pathogenic organisms and infections.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Figure 1 shows the most studied FP systems for sensitive molecules delivery. Several FP are used as base materials to fulfill the purpose; such as, polysaccharides (chitosan, starch and cellulose derivatives); proteins (gelatin, soy, casein and whey), poly(acrylic acid) (PAAc), glycerol, PEG and various gums such as guar, xanthan, PVP and PVA [ 19 , 20 ].…”
Section: Physical Modifications Of Fp To Enhance Oral Bioavailabilmentioning
confidence: 99%